Improving Mathematics Learning Outcomes Using Number Card Media In Class V Students Of SD Negeri Ngaglik, Sambi District, Boyolali - Mursid Sudartono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The cause of students mathematics learning outcomes is still low due to the lack of utilization of teaching media used by teachers in providing material. So, this is the factor that the grade V students at SD Negeri Ngaglik still have below the KKM with a total of 9 students and the percentage of scores below the KKM is 64%. Efforts made by the teacher to improve mathematics learning outcomes by applying number card media. This type of research is Classroom Action Research with the model of Kemmis and Mc Taggart (in Sunardi, 2007:13). The stages of the research started from the pre-action, cycle 1, cycle 2. The results of the pre-action research obtained data as much as 64% of students scored below KKM 70. After the action was taken using number cards, in cycle 1 it increased to 82%, in cycle 2 it increased to 91%. In conclusion, applying number card media is an effective way to improve learning outcomes with results above the KKM.